catena-Poly[[[(2-pyridone-kappa O)silver(I)]l-mu-2-pyridone-kappa O-2/O] hexafluoridophosphate] - Arman, H.D.; Miller, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The asymmetric unit of the polymeric title salt, {[Ag(C5H5-NO)(2)]PF6}(n), comprises an Ag I cation (located on a twofold axis), two 2-pyridone ligands (with distinct coordination modes), and half a PF6- anion (situated on a centre of inversion). The Ag I atom is in an approximately octahedral AgO6 coordination geometry, which is stabilized by intramolecular N-H center dot center dot center dot O hydrogen bonds. The result of the bridging mode of the 2-pyridone ligand is the formation of a supramolecular chain along the c axis; these are consolidated in the crystal by C-H center dot center dot center dot F interactions.